Synthesis of Copper and Silver Nanoparticles by Molecular Beam Method - Kurapov, Yurii; Litvin, Stanislav; Romanenko, Sergey M.; Didikin, Gennadii; Belyavina, Nadezhda (Micro and Nanosystems, 2018)
Background: Nanomaterials for medical applications, preparations with silver and copper nanoparticles attract special attention. Silver has stronger antimicrobial properties than does penicillin, biomycin and a number of other antibiotics. Nanoparticles of copper and copper oxide also exert a pronounced antibacterial effect. Objective: Further development and creation of medicines based on silver and copper nanoparticles require selecting a method for synthesis of nanoparticles that would ensure production of various nanomaterial compositions. Method: The method of electron beam evaporation and deposition of materials in vacuum opens up wide possibilities. The idea of using this approach is the possibility of simultaneous evaporation and deposition of mixed molecular flows of two substances onto a substrate. Results: The paper presents the results of investigation of the structure of porous condensates of Ag-NaCl and Cu-NaCl composition; chemical and phase compositions and dimensions of nanoparticles, produced from the vapour phase by EBPVD method. Silver and copper nanoparticles in a porous matrix have considerable sorption capacity relative to oxygen and moisture. Along to concentration change, phase composition of nanoparticles can be also controlled by heat treatment of the initial condensate produced at low condensation temperatures. Silver and copper nanoparticles can be converted into stable colloidal systems. Conclusion: Physical synthesis of silver and copper nanoparticles by EBPVD method allowed producing nanostructured material in the form of a dry substance for preparation of the required colloidal solutions. TGA method provides an indication of the processes of transformation in Ag-O system. Ag2O decomposes at the temperature of 460°C. Controlling the activity (size) of nanoparticles allows creating various compositions of nanomaterials, based on copper.
Keywords: molecular beam method